PERLINDUNGAN HUKUM CPMI KORBAN PENIPUAN OLEH P3MI: ANALISIS PERAN NEGARA - Ayu Novita Rahma (STKIP Subang, 2026)
This study explores the form and effectiveness of legal protection provided by the state to Prospective Indonesian Migrant Workers (CPMI) who experience fraud from Indonesian Migrant Worker Placement Companies (P3MI). The background of this study emphasizes that although international migration is usually motivated by economic goals to improve welfare, CPMI are often trapped in situations vulnerable to fraudulent practices, such as departure cancellations, overpayments, and document falsification. Using normative juridical methods and a descriptive qualitative approach, this study analyzes secondary data and complaint reports received by BP2MI from 2020 to 2025. The findings of this study indicate a significant discrepancy between legal provisions (Law No. 18 of 2017) and the reality, where thousands of CPMI continue to suffer losses due to a lack of professionalism on the part of P3MI and weak oversight by relevant agencies. The data obtained reveal various types of fraud, including passport confiscation, non-contractual employment, and debt arising from unreasonable placement fees. Despite the establishment of a dedicated agency (BP2MI/KP2MI) to provide administrative and technical protection, the current mechanisms are considered reactive. This study concludes that strengthening preventive oversight, changes to public policy, and stricter law enforcement are needed to address the structural dominance of P3MI and ensure legal certainty and justice for CPMI.